Enhancement of quality of social services through quality management system - Haburajová Ilavská, Lenka (Univerzita Pardubice, 2009)
The paper focuses on the social services issues that are a part of modern social policy. Social services are considered to be one of the forms of assistance provided for people and if they are to be organised and effective, it is inevitable to develop them from the point of view of the quality management system.
Keywords: social assistance; Social Services; providers; Financing; clients